Analysis of Mortality and Survival Rate of Liver Cancer in Zhejiang Province in China: A General Population-Based Study - Fang-Rong Fei; Ru-Ying Hu; Wei-Wei Gong; Jin Pan; Meng Wang (Canadian Journal of Gastroenterology and Hepatology)
Background. Few accurate up-to-date studies provide liver cancer mortality and survival information in Zhejiang province. This research aimed to depict the mortality and survival of liver cancer in Zhejiang province in China during 2005-2010. Methods. The data were collected from the Zhejiang Chronic Disease Surveillance Information and Management System, and the mortality rates of liver cancer were calculated by gender, age, and areas. Chinese population census in 2000 and Segi’s world population were used for age-standardized mortality rate. The observed and relative survival rates of liver cancer patients were analyzed. Results. The crude mortality rate of liver cancer was 32.11/105. The age-standardized mortality rate was 17.39/105 and 23.07/105 by Chinese population (ASIRC) and Segi’s world population (ASIRW), respectively. The crude liver cancer mortality rate and age-standardized rate in urban areas were lower than those of rural areas. The overall 1-, 3-, and 5-year observed survival (OS) rates of liver cancer patients were 38.61%, 21.65%, and 16.83%, respectively. The 1-, 3-, and 5-year relative survival (RS) rates of liver cancer patients were 39.49%, 23.27%, and 19.09%, respectively. Survival rate decreased obviously within 1 to 5 years and then leveled off. It was shown that the male overall survival rate was higher than the female one and the difference was statistically significant (P<0.05). Conclusions. Both lower mortality and better survival rates were observed in urban areas, compared to rural areas. Relevant parties including government, public resource, and propaganda department should devote enough attention to rural areas.